Association between in vivo bone formation and ex vivo migratory capacity of human bone marrow stromal cells. Issue 1 (December 2015) - Andersen, Rikke; Zaher, Walid; Larsen, Kenneth; Ditzel, Nicholas; Drews, Katharina; Wruck, Wasco; Adjaye, James; Abdallah, Basem; Kassem, Moustapha
Abstract Introduction There is a clinical need for developing systemic transplantation protocols for use of human skeletal stem cells (also known bone marrow stromal stem cells) (hBMSC) in tissue regeneration. In systemic transplantation studies, only a limited number of hBMSC home to injured tissues suggesting that only a subpopulation of hBMSC possesses "homing" capacity. Thus, we tested the hypothesis that a subpopulation of hBMSC defined by ability to form heterotopic bonein vivo, is capable of homing to injured bone. Methods We testedex vivo andin vivo homing capacity of a number of clonal cell populations derived from telomerized hBMSC (hBMSC-TERT) with variable ability to form heterotopic bone when implanted subcutaneously in immune deficient mice.In vitro transwell migration assay was used and thein vivo homing ability of transplanted hBMSC to bone fractures in mice was visualized by bioluminescence imaging (BLI). In order to identify the molecular phenotype associated with enhanced migration, we carried out comparative DNA microarray analysis of gene expression of hBMSC-derived high bone forming (HBF) clones versus low bone forming (LBF) clones. Results HBF clones were exhibited higherex vivo transwell migration and following intravenous injection, betterin vivo homing ability to bone fracture when compared to LBF clones. Comparative microarray analysis of HBF versus LBF clones identified enrichment of gene categories of chemo-attraction, adhesion and migration associated genes. Among these, platelet-derived growth factor receptor (PDGFR) α and β were highly expressed in HBF clones. Follow up studies showed that the chemoattractant effects of PDGFin vitro was more enhanced in HBF compared to LBF clones and this effect was reduced in presence of a PDGFRβ-specific inhibitor: SU-16 f. Also, PDGF exerted greater chemoattractant effect on PDGFRβ+ cells sorted from LBF clones compared to PDGFRβ- cells. Conclusion Our data demonstrate phenotypic and molecular association betweenin vivo bone forming ability and migratory capacity of hBMSC. PDGFRβ can be used as a potential marker for the prospective selection of hBMSC populations with high migration and bone formation capacities suitable for clinical trials for enhancing bone regeneration.